A physiologically based biopharmaceutics modeling (PBBM) framework for characterizing formulation-dependent food effects: Paving the road towards fed state virtual BE studies for itraconazole amorphous solid dispersions - Rudolph, Niklas; Charbe, Nitin; Plano, David; Shoyaib, Abdullah Al; Pal, Arindom; Boyce, Heather; Zhao, Liang; Wu, Fang; Polli, James; Dressman, Jennifer; Cristofoletti, Rodrigo (European journal of pharmaceutical sciences, 2025)
This study leverages physiologically based biopharmaceutics modeling (PBBM) to predict the clinical performance of two itraconazole (ITRA) amorphous solid dispersions (ASDs), Sempera® and Tolsura®, under fasted and fed state conditions, exploring the potential of PBBM in predicting formulation-specific food interactions. The ITRA formulations were subjected to extensive in vitro biopharmaceutical testing, including solubility studies and dissolution tests under fasted and fed state conditions, revealing significant differences in dissolution behaviors between Sempera® and Tolsura®. The impact of food and hypochlorhydria on drug absorption was evaluated using a stepwise mechanistic deconvolution-reconvolution PBBM approach, integrating fundamental parameters based on the in vitro data into the final model. Our model not only successfully predicted the effects of acid reducing agents (ARA) and food on the oral absorption of ITRA, but also captured the between-subject variability, demonstrating the utility of this approach in understanding the complex interplay between drug, formulation, and gastrointestinal environment. Most importantly, the PBBM was able to accurately predict the positive impact of food on the absorption of Sempera® and the negative food effect of Tolsura®. The findings highlight the importance of considering formulation characteristics and gastrointestinal physiology, underscoring the potential of PBBM in bioequivalence (BE) assessment of generic formulations under varying physiological conditions, including in the fed state and in hypochlorhydric patients. The successful application of this stepwise and mechanistic PBBM approach suggests a potential pathway for streamlining drug development and may contribute to more informed decision-making for BE assessment. [Display omitted]